Diversity and uses of Zingiberaceae in Nam Nao National Park, Chaiyaphum and Phetchabun provinces, Thailand, with a new record for Thailand - Saensouk, Surapon; Saensouk, Piyaporn; Pasorn, Pattana; Chantaranothai, Pranom (Agriculture and Natural Resources, 2016)
Three tribes, 12 genera and 38 species of the ginger family (Zingiberaceae) along five routes in Nam Nao National Park were surveyed between January 2012 and December 2013 to determine their diversity, ecological data, phenology, uses and conservation status. The highest diversity was found in the tribe Zingibereae (6 genera and 21 species), of which the genera Curcuma and Zingiber comprised the highest number species (eight species each). A species key was constructed based on morphology. The ginger family was found in four forest-types-deciduous dipterocarp forest, mixed deciduous forest, dry evergreen forest and pine forest. The most flowering bloom of the ginger family in Nam Nao National Park was during March to August and the most fruiting bloom was during June to September. The popular uses of Zingiberaceae were as a food, spice, in medicine, as ornamentation and in rituals. Eight species have been evaluated as of least concern and are presented in the IUCN Red List, while two rare species were reported in Thailand Red Data: Plants, while six rare Zingiberaceae species were identified based on the evaluation criteria of Saensouk (2011). Four species were endemic to Thailand. Moreover, Etlingera yunnanensis (T. L. Wu & S. J. Chen) R. M. Smith was a new record for Thailand.